Regulatory barriers to equity in a health system in transition: a qualitative study in Bulgaria - Spencer Nick J; Blackburn Clare M; Rechel Boika; Rechel Bernd (BMC, 2011)
Abstract Background Health reforms in Bulgaria have introduced major changes to the financing, delivery and regulation of health care. As in many other countries of Central and Eastern Europe, these included introducing general practice, establishing a health insurance system, reorganizing hospital services, and setting up new payment mechanisms for providers, including patient co-payments. Our study explored perceptions of regulatory barriers to equity in Bulgarian child health services. Methods 50 qualitative in-depth interviews with users, providers and policy-makers concerned with child health services in Bulgaria, conducted in two villages, one town of 70,000 inhabitants, and the capital Sofia. Results The participants in our study reported a variety of regulatory barriers which undermined the principles of equity and, as far as the health insurance system is concerned, solidarity. These included non-participation in the compulsory health insurance system, informal payments, and charging user fees to exempted patients. The participants also reported seemingly unnecessary treatments in the growing private sector. These regulatory failures were associated with the fast pace of reforms, lack of consultation, inadequate public financing of the health system, a perceived "commercialization" of medicine, and weak enforcement of legislation. A recurrent theme from the interviews was the need for better information about patient rights and services covered by the health insurance system. Conclusions Regulatory barriers to equity and compliance in daily practice deserve more attention from policy-makers when embarking on health reforms. New financing sources and an increasing role of the private sector need to be accompanied by an appropriate and enforceable regulatory framework to control the behavior of health care providers and ensure equity in access to health services.